A Novel Posterior Trench Approach Involving Percutaneous Endoscopic Cervical Discectomy for Central Cervical Intervertebral Disc Herniation. Issue 1 (February 2019) - Yu, Ke-Xiao; Chu, Lei; Chen, Liang; Shi, Lei; Deng, Zhong-Liang
Abstract : Objective: This report describes a novel posterior trench approach involving percutaneous endoscopic cervical discectomy (PECD) for central cervical intervertebral disc herniation (CIVDH) and an evaluation of the feasibility, safety, and short-term clinical effect of this approach. Background Context: Central CIVDH is considered the contraindication for posterior PECD. Materials and Methods: A single-center retrospective observational study was performed with 30 patients managed with posterior PECD using the trench approach for symptomatic single-level central CIVDH. Primary outcomes included the measures of bodily pain and physical function based on the SF-36 and modified MacNab criteria. Radiographical follow-up included the static and dynamic cervical plain radiographs, computed tomographic scans, and magnetic resonance images. Results: A positive clinical response for symptom relief was achieved in all patients. The postoperative MRI showed total removal of the herniated disc. Conclusions: As a supplement to the described surgical techniques of PECD, this trench approach provides novel access for the treatment of CIVDH, especially for the central type. The advantages of this technique include the provision of access to decompress the ventral region of the thecal sac and the ability to avoid damage to the facet joint. The steep learning curve might be a major disadvantage, and the sample volume is a limitation of the study; the effectiveness and reliability of the trench approach should be further verified in a comparative cohort study with a large volume of patients. Abstract : Supplemental Digital Content is available in the text.